Ant colony algorithm for rational transit network design of urban passenger transport; Lifelong wellbeing in the world (WELLSO-2014) - Martynova Yu. A. Yulia Alekseevna; Shutova Yu.O.; Martynov Ya. A Yaroslav Andreevich; Kochegurova E. A. Elena Alekseevna (2014, 2014)
Title screen.